Physis and nomos: The nature of equality in poppers and strauss readings of Plato - Colen,José (2013)
Striving for equality has been often, if not always, at the heart of the ethos of democratic regimes, even when practices fall short of such ambitious goal. The trend towards an ever increasing equality still faces an important and pervasive limitation, i.e. citizenship is not a right shared by all, but a privilege of birth, or descent, or autochthony. This problem was voiced in Platos dialogue Menexenus: is democracy viable if no historical ties or common culture justifies solidarity and bearable sharing democratic burdens? Is social equality of the citizens a condition forcing to seek legal equality or an enemy of excellence? In spite of the enormous differences between Poppers and Strauss agendas and even their ideals, both chose to explore the normative foundation of democracy by confrontation with Plato and his predecessors. Karl Popper in The Open society criticized Platos arguments against equality proposing an idiosyncratic interpretation of the controversy on Nature and Convention. Leo Strauss in his conferences on Natural right and history also elaborated on the emergence of the concepts of Physis and Nomos confronting Plato against classical conventionalism. This paper engages Popper and Strauss in a fictive debate on the foundations of political equality.